Long-term follow-up of a retrospective comparison of reduced-intensity conditioning and conventional high-dose conditioning for allogeneic transplantation from matched related donors in myelodysplastic syndromes - Martino, R; Henseler, A; van Lint, M; Schaap, N; Finke, J; Beelen, D; Vigouroux, S; Alessandrino, E P; Mufti, G J; Veelken, J H; Bruno, B; Yakoub-Agha, I; et al. (Bone marrow transplantation, 2017)
This study shows the long-term updated outcomes of a multicenter retrospective study which analyzed 843 patients with myelodysplastic syndrome (MDS) who underwent transplantation with an HLA-identical sibling donor with either reduced-intensity conditioning (RIC) in 213 patients, or standard myeloablative conditioning (MAC) in 630 patients. In multivariate analysis, the 13-year relapse rate was significantly increased after RIC (31% after MAC vs 48% in RIC; HR, 1.5; 95% CI, 1.1-1.9; P=0.04), but with no differences in overall survival (OS) (30% after MAC vs 27% in RIC; P=0.4) and PFS (29 vs 21%, respectively, P=0.3). Non-relapse mortality was higher in MAC (40 vs 31%; P=0.1), especially in patients older than 50 years (50 vs 33%, P<0.01). In addition, long-term follow-up confirms the importance of other variables on 13-year OS, mainly MDS risk category, disease phase, cytogenetics and receiving a high donor cell dose, irrespective of the conditioning regimen used.
Keywords: analýza přežití; testování histokompatibility; retrospektivní studie; Histocompatibility Testing; Myelodysplastic Syndromes; následné studie; Siblings; Tissue Donors; Aged; Case-Control Studies; senioři; příprava pacienta k transplantaci; dárci tkání; Survival Analysis; Follow-Up Studies; myelodysplastické syndromy; Transplantation Conditioning; lidé; studie případů a kontrol; Humans; sourozenci; Retrospective Studies; lidé středního věku; Middle Aged